Learning Analysis of the Long Jump Material Using the Playing Method for Junior High School Students - Rubi Yatno (Jurnal Serambi Ilmu, 2022)
This study aims to determine how the learning outcomes of the squat stylelong jump using the play method in class VIII students of State Junior HighSchool 1 Kuburaya. The form of research used in this research isexperimental research with two stages consisting of planning,implementation, observation, reflection, and conclusion. The subjects in thisstudy were Class VIII students, totaling 35 students. The results ofimproving soccer passing learning using the inside of the foot are obtainedby comparing the observation value with the initial test before the actionknown as "pre-stage" and the score at stage 1 then stage 2. Based on theresults of observations that have been carried out, there is an increase instudent scores, namely in the pre-stage completeness of students onlyreached 28% then at stage 1 the completeness increased to 50% and at stage2 there was an increase in completeness to 84% it can be concluded that theplaying method applied was successful in improving students' long jumplearning outcomes. Playing has been proven to improve learning the squatstyle long jump. This is evidenced by the increase in the squatting style longjump learning which is quite good, which is an increase in student scores ateach stage.